2011
DOI: 10.2475/01.2011.02
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic significance of ductile deformation in low-grade sandstones in the mesozoic Otago subduction wedge, New Zealand

Abstract: BSTRACT. This study demonstrates how ductile strain measurements can determine the tectonic evolution of a large and long-lived suhduction wedge. We provide a synthesis of the geology of the South Island of New Zealand, with an emphasis on a wedge tectonics perspective that contrasts with a traditional view that interprets New Zealand geology in the context of terrane collision and accretion. We argue that the Otago subduction wedge evolved in a steady fashion throughout its 290 to 105 Ma history in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…In addition, the spatially steep P – T gradient within the B unit suggests ductile thinning of this unit. Ductile thinning within an accretionary wedge may be accomplished by orogen‐parallel extension as proposed for the D1 stage of the Sanbagawa and Mikabu units in the study area (Wallis, ) or significant volume loss by pressure solution (Feehan & Brandon, ; Rahl, Brandon, Deckert, Ring, & Mortimer, ). Microstructural observation suggests that pressure solution mass transfer is the main deformation mechanism of the B unit (Figure d,e).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spatially steep P – T gradient within the B unit suggests ductile thinning of this unit. Ductile thinning within an accretionary wedge may be accomplished by orogen‐parallel extension as proposed for the D1 stage of the Sanbagawa and Mikabu units in the study area (Wallis, ) or significant volume loss by pressure solution (Feehan & Brandon, ; Rahl, Brandon, Deckert, Ring, & Mortimer, ). Microstructural observation suggests that pressure solution mass transfer is the main deformation mechanism of the B unit (Figure d,e).…”
Section: Discussionmentioning
confidence: 99%
“…Otago Schist tectonic models have changed from those emphasizing Jurassic terrane collision and crustal thickening [e.g., Mortimer , 1993] to those emphasizing Cretaceous extensional exhumation [e.g., Deckert et al , 2002; Forster and Lister , 2003; Gray and Foster , 2004] to those emphasizing an evolving accretionary wedge [e.g., Breeding and Ague , 2002; Rahl et al , 2011]. All are probably applicable, with convergent accretionary wedge structures preserved on the schist flanks and extensional fabrics in the core region of the Otago Antiform [ Stallard and Shelley , 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Kamp (2001) suggested exhumation of Otago-Haast Schist began at ϳ135 Ma in response to the accretionary wedge achieving steady state conditions. The concept of different transport paths for different rocks was taken further by Rahl et al (2011), who suggested rocks on the eastern (prowedge) side of the Otago-Haast culmination had been frontally accreted, whereas those on the western (retrowedge) side had been underplated.…”
Section: Outboard Accretionary Wedgementioning
confidence: 99%